Do the novelty and type of innovation affect the performance of firms? A case study for Ecuador - Grace Carolina Guevara Rosero; Jonathan Rafael Quijia Pillajo; José Fernando Ramirez Álvarez; Oscar Omar Acero Almachi (Investigaciones Regionales - Journal of Regional Research)
Since innovation is a productivity driver that leads to economic growth, the case of a developing country, Ecuador, is studied. The aim of this paper is to measure the causal effect of innovation on firms’ productivity by distinguishing the type of innovation, namely, in products, in process, in organization and in marketing. To do so, an endogenous switching model is estimated using the Science, Technology and Innovation Activity Survey. The results indicate that the productivity loss is higher for innovating firms if they stop innovating than the productivity gain of non-innovating firms if they engage in innovation. The difference between the productivity losses and gains depends on the type of innovation.